2019
DOI: 10.1177/2055207619853397
|View full text |Cite
|
Sign up to set email alerts
|

Facebook support for breastfeeding mothers: A comparison to offline support and associations with breastfeeding outcomes

Abstract: Objectives For breastfeeding mothers, online support groups through Facebook may be a more convenient and preferred source for accessing breastfeeding information and support, but few studies exist that examine the use of Facebook groups specifically for breastfeeding support. This study explores the sources of support among users of Facebook breastfeeding support groups and a possible mechanism by which support received on Facebook may translate to behavioral outcomes among breastfeeding mothers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(106 citation statements)
references
References 39 publications
(68 reference statements)
1
83
1
5
Order By: Relevance
“…There already are breastfeeding support groups led by midwives in Spain nowadays [42], but they do not follow a common structure or systematization that allows for impact assessment. This project aims to develop a common structure based on prenatal counselling, antenatal classes and a follow-up over the first 6 months of the newborn's life, by means of monthly group sessions and mother-tomother support through social networks (Facebook and WhatsApp), a support resource described in the previous literature [28], and to assess their efficacy. This will help elaborate a guide which can offer a direction to those professionals who wish to set up a breastfeeding support group in their primary health centre.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There already are breastfeeding support groups led by midwives in Spain nowadays [42], but they do not follow a common structure or systematization that allows for impact assessment. This project aims to develop a common structure based on prenatal counselling, antenatal classes and a follow-up over the first 6 months of the newborn's life, by means of monthly group sessions and mother-tomother support through social networks (Facebook and WhatsApp), a support resource described in the previous literature [28], and to assess their efficacy. This will help elaborate a guide which can offer a direction to those professionals who wish to set up a breastfeeding support group in their primary health centre.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from these monthly meetings, the participants will have the choice of interacting with each other, with other lactating women, and with the reference midwife, using Facebook and WhatsApp groups created for that purpose. This way, mother-to-mother support can be reinforced and the resolution of doubts on the subject through Information and Communication Technologies (ICTs) [28] can be assessed. They will also have the option of arranging an individual appointment with their reference midwife, as well as the usual postnatal care.…”
Section: Description Of the Intervention Intervention Groupmentioning
confidence: 99%
“…Penelitian lain juga mengungkapkan bahwa di era digital sekarang ini, dukungan terhadap ibu menyusui dapat dilakukan melalui facebook, karena ibu muda sekarang banyak yang menggunakan media sosial ini dan mereka dapat berinteraksi melalui facebook dalam waktu yang lebih lama dan sesuai minat mereka (Robinson, Lauckner, Davis, Hall, & Anderson, 2019). Oleh karena itu kedepannya berawal dari pembentukan KP-ASI ini nantinya dapat diinisiasi pembentukan kelompok pendukung ASI melalui facebook dengan grup tertutup supaya tetap ada privacy ketika membicarakan hal yang dianggap tabu.…”
Section: Gambar 7 Hasil Lomba Pelatihan Kader Kp-asiunclassified
“…Personalized information and more interaction are characteristics that women demand (Halili et al, 2018). This personalized information is highlighted as essential for BF maintenance by mothers and health professionals (Garner et al, 2016; Robinson et al, 2019). A previous study revealed that LactApp queries increased between July 2016 and June 2019 and the trend of queries has grown according to Prais–Winsten autoregressions based on the Durbin–Watson model (article under peer review).…”
Section: Discussionmentioning
confidence: 99%
“…Personalized information and more interaction are characteristics that women demand(Halili et al, 2018). This personalized information is highlighted as essential for BF maintenance by mothers and health professionals(Garner et al, 2016;Robinson et al, 2019). A previous study revealed that LactApp queries increased between July 2016 and June 2019 and the trend of queries has grown according to Prais-Winsten autoregressions based on the Durbin-Watson model (article under peer review).Different factors can contribute to shorter BF durations, including mother's perception of insufficient milk supply, nipple or breast pain, lack of social support, lack of confidence, physical and social embarrassment, comfort and trust in formula(Morrison et al, 2019;Schindler-Ruwisch et al, 2018), which are associated with difficulty with latch and position, and the presence of infant tonguetie, among other factors(Kent et al, 2015).…”
mentioning
confidence: 99%